Cultivars and lines added to the gene pool of VIR’s durum wheat collection in 2000–2019. - O. A. Lyapunova; A. S. Andreeva (Труды по прикладной ботанике, генетике и селекции)
Replenishment of the collection of durum wheat (Triticum durum Desf.), like any other crop collection held by VIR, is a permanent process aimed at expanding the geographic, morphological and agrobiological diversity of the crop’s gene pool. A special status in this process is given to the achievements of domestic breeders, whose cultivars and lines over time remain only in the ex situ collection and constitute the national heritage of Russia. Replenishment, along with conservation, studying and sharing with the users, is a mandatory task when managing a plant germplasm collection. It can be fulfilled by sending requests for seeds to other genebanks, through the exchange with the collections of foreign research centers, contacts with individual breeders or breeding centers in Russia, or when crop cultivars are submitted to VIR from the State Register of Breeding Achievements Approved for Utilization in Russia. Besides, new accessions are added to the genebank by collecting missions.Descriptions have been made for 570 accessions included in the main catalogue of VIR’s durum wheat collection from 2000 to 2019. They originated from 28 countries of Europe, Asia, the Near East, Africa and North America, and from 16 regions of Russia.The durum wheat collection of VIR was replenished with accessions interesting both from the geographic and agrobiological viewpoints. Cultivars developed by domestic breeders are included in the global genetic resources collection primarily with the purpose of their conservation and comprehensive utilization, both now and in the future.